1995
DOI: 10.1093/infdis/172.5.1388
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Haemophilus influenzae Strains and Strain Variants Coexist in the Respiratory Tract of Patients with Cystic Fibrosis

Abstract: To investigate the epidemiology of nontypeable Haemophilus influenzae in the respiratory tract of cystic fibrosis (CF) patients, H. influenzae isolates from sputum specimens of 40 CF patients were analyzed longitudinally for 2 years. The isolates were characterized by analysis of the major outer membrane protein (MOMP) patterns. MOMP variant H. influenzae strains were discriminated from distinct strains by randomly amplified polymorphic DNA analysis of genomic DNA. Multiple H. influenzae strains and MOMP varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
86
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 15 publications
5
86
2
1
Order By: Relevance
“…Past studies have demonstrated that H. influenzae colonization of the pharynx is characterized by rapid bacterial turnover (9,12,50,58) and carriage of multiple strains at any one time (18,37,43,52,58). Previous studies have demonstrated a 62% week-to-week turnover rate of H. influenzae isolated from healthy children attending day care; 37 to 43% of throat cultures contained two or more genetically distinct strains (range, zero to five) (14,56).…”
mentioning
confidence: 99%
“…Past studies have demonstrated that H. influenzae colonization of the pharynx is characterized by rapid bacterial turnover (9,12,50,58) and carriage of multiple strains at any one time (18,37,43,52,58). Previous studies have demonstrated a 62% week-to-week turnover rate of H. influenzae isolated from healthy children attending day care; 37 to 43% of throat cultures contained two or more genetically distinct strains (range, zero to five) (14,56).…”
mentioning
confidence: 99%
“…An opportunistic pathogen, NTHI resides asymptomatically in the upper airways of humans but can disseminate into privileged anatomical locations, causing infections such as otitis media, sinusitis, and pneumonia (47). NTHI is also one of the most prevalent microorganisms found in the lungs of patients with exacerbations of chronic obstructive pulmonary disease (48,49,60) and cystic fibrosis (23,43,58). An effective vaccine against NTHI strains has not yet been discovered, likely due to high variability of surface antigens between strains (60).…”
mentioning
confidence: 99%
“…To better study the persistence of this bacterium, several typing methods have been applied: serotyping, biotyping, outer membrane protein (OMP) electrophoresis, and genotyping methods, such as random PCR (1,17,18,24,35).…”
mentioning
confidence: 99%